2014
DOI: 10.1007/s10877-014-9596-0
|View full text |Cite
|
Sign up to set email alerts
|

The evaluation of a non-invasive respiratory volume monitor in surgical patients undergoing elective surgery with general anesthesia

Abstract: Continuous respiratory assessment is especially important during post-operative care following extubation. Respiratory depression and subsequent adverse outcomes can arise due to opioid administration and/or residual anesthetics. A non-invasive respiratory volume monitor (RVM) has been developed that provides continuous, real-time, measurements of minute ventilation (MV), tidal volume (TV), and respiratory rate (RR) via a standardized set of thoracic electrodes. Previous work demonstrated accuracy of the RVM v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 12 publications
0
26
0
Order By: Relevance
“…An over 24-h study by Voscopoulos et al showed that RVM has similar accuracy and high correlation with spirometry in measuring MV, TV, and RR, based on comparison between RVM and ventilator measurements in both intubated and non-intubated patients (56, 57). It is also noteworthy that the patients’ average RR difference between the RVM measurements and the manual counting of individual breaths, by the technician, during the 24-ho study was 0.0 breaths/min, demonstrating that the RVM is extremely accurate in measuring RR (56).…”
Section: Rvm For Minute Volumementioning
confidence: 99%
“…An over 24-h study by Voscopoulos et al showed that RVM has similar accuracy and high correlation with spirometry in measuring MV, TV, and RR, based on comparison between RVM and ventilator measurements in both intubated and non-intubated patients (56, 57). It is also noteworthy that the patients’ average RR difference between the RVM measurements and the manual counting of individual breaths, by the technician, during the 24-ho study was 0.0 breaths/min, demonstrating that the RVM is extremely accurate in measuring RR (56).…”
Section: Rvm For Minute Volumementioning
confidence: 99%
“…In an analysis of 178 patients receiving IV PCA, episodes of desaturation (defined as SPO 2 <90%) occurred in 12% of patients, within a mean timeframe of about 24 hours after initiation of PCA. 28,29 Patients older than 65 years and the morbidly obese were most likely to experience these episodes. Occurrences of decreased respiratory rate or bradypnea (defined as <10 breaths per minute lasting Q3 minutes) were also observed in these study populations.…”
Section: Implications For Nurse Executivesmentioning
confidence: 99%
“…Minute ventilation monitors are user friendly and may be found more effective than pulse oximetry in patients taking opioids for pain control. 29 Regardless of the type of monitor, nurse leaders should consider training clinicians on the use of continuous monitoring during sleep.…”
Section: Implications For Nurse Executivesmentioning
confidence: 99%
“…They found that abnormal breathing patterns are extremely common. Voscopoulos et al [14,15,16] have studied minute ventilation, tidal volume and respiratory rate of postoperative subjects using impedancebased electrodes placed to a subject's body. In addition to these, Masa et al [17] showed that respiratory effort-related arousals in sleep apnea patients could be identified satisfactorily by assessing the morphology of the thoracoabdominal bands output signal.…”
Section: Introductionmentioning
confidence: 99%